N-hexane Extract and Fraction of Green Tea as Antiproliferation of MCM-B2 Breast Cancer Cells In Vitro - Lisni Noraida; Maria Bintang; Bambang Pontjo Priosoeryanto (Current Biochemistry, 2019)
Green tea (Camellia sinensis) is one of tradisional plants that have potential as anticancer. Thesample used in this research was commercial green tea extract. The purpose of this study was to test theantiproliferation activity of green tea extract on breast cancer cell MCM-B2 in vitro. Green tea extract wasfractionated using three solvents, ie water, ethanol 70%, and n-hexane. Extract and water fraction of greentea have Lethality Concentration 50 (LC50) value of more than 1000 ppm. Fractions of ethanol 70% and nhexane had an LC50 value of 883.48 ppm and 600.56 ppm, respectively. The results of phytochemicalscreening of green tea extract are flavonoids, tannins, and saponins, while the phytochemical screeningresults of n-hexane fraction are flavonoids and tannins. Antiproliferation activity was tested on breast cancercells MCM-B2 and normal cells Vero by tripan blue staining method. The highest MCM-B2 cell inhibitoryactivity was achieved at a concentration of 13000 ppm green tea extract and 1000 ppm of n-hexane fraction,59% and 59%, respectively. The extract and n-hexane fraction of green tea are not toxic to normal Verocells characterized by not inhibiting normal cell proliferation.